Elevated EVL methylation level in the normal colon mucosa is a potential risk biomarker for developing recurrent adenomas - Yu, Ming; Carter, Kelly T.; Baker, Kelsey K.; Redman, Mary W.; Wang, Ting; Vickers, Kathy; Li, Christopher I.; Cohen, Stacey A.; Krane, Mukta; Ose, Jennifer; Gigić, Biljana; Figueiredo, Jane C.; et al. (Cancer epidemiology, biomarkers & prevention, 2023)
Individuals with adenomatous colorectal polyps undergo repeated colonoscopy surveillance to identify and remove metachronous adenomas. However, many patients with adenomas do not develop recurrent adenomas. Better methods to evaluate who benefits from increased surveillance are needed. We evaluated the use of altered EVL methylation as a potential biomarker for risk of recurrent adenomas.Patients with ≥1 colonoscopy had EVL methylation (mEVL) measured with an ultra-accurate methylation-specific droplet digital PCR assay on normal colon mucosa. The association between EVL methylation levels and adenoma or colorectal cancer was evaluated using three case/control definitions in three models: unadjusted (model 1), adjusting for baseline characteristics (model 2), and an adjusted model excluding patients with colorectal cancer at baseline (model 3).Between 2001 and 2020, 136 patients were included; 74 healthy patients and 62 patients with a history of colorectal cancer. Older age, never smoking, and baseline colorectal cancer were associated with higher levels of mEVL (P ≤ 0.05). Each log base 10 difference in mEVL was associated with an increased risk of adenoma(s) or cancer at/after baseline for model 1 [OR, 2.64; 95% confidence interval (CI), 1.09-6.36], and adenoma(s) or cancer after baseline for models 1 (OR, 2.01; 95% CI, 1.04-3.90) and model 2 (OR, 3.17; 95% CI, 1.30-7.72).Our results suggest that EVL methylation level detected in the normal colon mucosa has the potential to be a biomarker for monitoring the risk for recurrent adenomas.These findings support the potential utility of EVL methylation for improving the accuracy for assigning risk for recurrent colorectal adenomas and cancer.
Gesehen am 16.11.2023